Current Strategies and Future Directions of Wearable Biosensors for Measuring Stress Biochemical Markers for Neuropsychiatric Applications - Zach Sheffield; Priyanka Paul; Shraddha Krishnakumar; Dipanjan Pan (Advanced Science)
Abstract Most wearable biosensors aimed at capturing psychological state target stress biomarkers in the form of physical symptoms that can correlate with dysfunction in the central nervous system (CNS). However, such markers lack the specificity needed for diagnostic or preventative applications. Wearable biochemical sensors (WBSs) have the potential to fill this gap, however, the technology is still in its infancy. Most WBSs proposed thus far target cortisol. Although cortisol detection is demonstrated as a viable method for approximating the extent and severity of psychological stress, the hormone also lacks specificity. Multiplex WBSs that simultaneously target cortisol alongside other viable stress‐related biochemical markers (SBMs) can prove to be indispensable for understanding how psychological stress contributes to the pathophysiology of neuropsychiatric illnesses (NPIs) and, thus, lead to the discovery of new biomarkers and more objective clinical tools. However, none target more than one SBM implicated in NPIs. Till this review, cortisol's connection to dysfunctions in the CNS, to other SBMs, and their implication in various NPIs has not been discussed in the context of developing WBS technology. As such, this review is meant to inform the biosensing and neuropsychiatric communities of viable future directions and possible challenges for WBS technology for neuropsychiatric applications.